Elementary English Acquisition - Beth Anne Cherry; Renee Ford; Kathy Mueller (Networks: An Online Journal for Teacher Research, 2004)
From the beginning of chapter one in Learning English at School, the author, Colleen Toohey, emphasizes that social interactions have a pivotal role in young children's second language learning. She begins by analyzing the data of several theorists and researchers, such as Snow, Vygotsky, and Bakhtin, she had reviewed to develop the theory and methodology for her study. Toohey does a nice job relating her own experiences and observations to the presented theories.